Research 'Is a Hadith Narrator - Tetep Abdulatip; Tajul Arifin; Muhamad Chaedar Rafiq (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to examine the meaning of ‘adalah, the levels of ta’dil and its impact on the narration of the hadith brought, and the rules used in ta’dil. The research method used is a qualitative research method by collecting written data sources, both primary data from books and secondary data from online digital based with a library research approach to facilitate the preparation of this article. The results and discussion of this study conclude that the assessment of ‘adalah (justice) includes aspects of faith and morals; there are six levels and six rules in carrying out ta’dil.